2021
DOI: 10.36547/nbc.1062
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of zinc from aqueous solution using algae and plant biomass

Abstract: In the present study, the sorption capacity of plant biomass has been studied; particularly the ability of biomass algae Chlorella vulgaris, filamentous green algae Spirogyra sp. and roots, stems and leaves of an invasive plant Reynoutria japonica to bind up Zn2+ ions. The results of this biosorption study revealed that the rate and extent of uptake were affected by pH level, contact time and initial metal concentration. The maximum uptake of metal ions was obtained at pH 6.0. The equilibrium sorption data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Biosorption is an innovative technology that employs inactive and dead biomass for the removal and recovery of metals from aqueous solutions (Romera et al, 2007;Cui and Grace, 2007). Various biomasses such as bacteria (Ridha, 2011), sludge (Ali, 2011), yeast (Sulaymon et al, 2010), algae (Kratochvil, 1997), fungi (Brady et al, 1999) and plants (Melcakova and Ruzovic, 2010) have been used to adsorb metal ions from the environment. Among the most promising types of biosorbents studied are algal biomass (Romera et al, 2006;Figueria et al, 2000), algal biomass have been reported to have high metal binding capacities due to their containing of functional groups on the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…Biosorption is an innovative technology that employs inactive and dead biomass for the removal and recovery of metals from aqueous solutions (Romera et al, 2007;Cui and Grace, 2007). Various biomasses such as bacteria (Ridha, 2011), sludge (Ali, 2011), yeast (Sulaymon et al, 2010), algae (Kratochvil, 1997), fungi (Brady et al, 1999) and plants (Melcakova and Ruzovic, 2010) have been used to adsorb metal ions from the environment. Among the most promising types of biosorbents studied are algal biomass (Romera et al, 2006;Figueria et al, 2000), algal biomass have been reported to have high metal binding capacities due to their containing of functional groups on the cell wall.…”
Section: Introductionmentioning
confidence: 99%